2020
DOI: 10.1111/1753-6405.12953
|View full text |Cite
|
Sign up to set email alerts
|

Closing the gap between rhetoric and practice in strengths‐based approaches to Indigenous public health: a qualitative study

Abstract: Objective: To understand strengths‐based practice as articulated by urban Indigenous community workers and to consider its application for public health approaches to Australian Indigenous health advancement. Methods: Semi‐structured interviews with community workers from an urban Indigenous community. Interviews were video and audio recorded and transcribed verbatim. Data were analysed using thematic analysis, using an Indigenist research framework. Results: For our participants (11 Indigenous and one non‐Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 9 publications
0
54
0
Order By: Relevance
“…NARN has been active in networking, championing and researching service‐learning student placements. Based on the principles of community co‐design to ensure community needs are central and Indigenous ways of knowing, being and doing are privileged, 13 NARN‐championed services have focused on four strength‐based themes: children developing well, young people growing up well, adults staying strong, and older people ageing well in place. Underlying these themes are the IAHA and community partnerships to ensure that culturally safe and responsive practice is prioritised 14,15 .…”
Section: Student Support Of Allied Health Servicesmentioning
confidence: 99%
“…NARN has been active in networking, championing and researching service‐learning student placements. Based on the principles of community co‐design to ensure community needs are central and Indigenous ways of knowing, being and doing are privileged, 13 NARN‐championed services have focused on four strength‐based themes: children developing well, young people growing up well, adults staying strong, and older people ageing well in place. Underlying these themes are the IAHA and community partnerships to ensure that culturally safe and responsive practice is prioritised 14,15 .…”
Section: Student Support Of Allied Health Servicesmentioning
confidence: 99%
“…73 It has been suggested that governments resist giving greater power to Aboriginal people as this could destabilise entrenched colonial ideas and practices. 74 Furthermore, Aboriginal peoples' "ideas" may not fit with "needs" as defined by Western policy-makers. 75 Aboriginal organisations frequently recommended structural and environmental strategies in their consultation submissions, but policy documents were more likely to recommend behavioural approaches.…”
Section: Ideasmentioning
confidence: 99%
“…A strengths-based approach provides an alternate paradigm for considering and addressing smoking cessation during pregnancy for Indigenous women [20][21][22]. Here, deficit views of Indigenous people's health and wellbeing that are all too common in mainstream health promotion [23] are replaced with recognition and place for the inherent strength of Indigeneity in providing a solid foundation from which smoking cessation programs can be built.…”
Section: Introductionmentioning
confidence: 99%